The Influence of Village Fund Allocation and Village Income on Infrastructure Development in Four Villages in Parungkuda District - Ardi, Dian; Suparman, Dadang (Formosa Journal of Sustainable Research, 2024)
This research was carried out in four villages in Parungkuda sub-district, Sukabumi district, including Parungkuda Village, Sundaauthor Village, Kompa Village, Langensari Village. The aim of this research is to find out whether there is an influence of Village Fund Allocation income and Village Income on Infrastructure Development in four villages in Parungkuda sub-district, Sukabumi district. The research method used is a quantitative method. The population in this study is the village financial report for 2019-2021. Based on the research results of the normality test with a value of 0.200 > 0.05, the multicollinearity test results VIF 0.10 <10.00, the Durbin-Waston autocorrelation test 2.4206, Village fund allocation Based on the value of r, calculate the Pearson correlation for the Village Fund Allocation variable (X1) = -0.206 < r table n = 12 samples from two-tailed test 0.576. Village income Based on r calculated Pearson correlation variable Original Village Income (X2) 0.395 < r table n = 12 samples from two-way test 0.576. So the Village Original Income variable (X2) has no positive relationship or correlation with the Infrastructure Development variable (Y) with a Pearson Correlation degree of 0.395, which is in the very low correlation category. And testing the hypothesis simultaneously with a value of 0, .394 > 0.05 means that the village fund allocation and village income variables simultaneously have no effect on the infrastructure development variable